UJI AKTIVITAS ANTIBAKTERI EKSTRAK MAKROALGA Kappaphycus Striatum TERHADAP BAKTERI Pseudomonas Aerugimunosa: TESTING THE ANTIBACTERIAL ACTIVITY OF Kappaphycus Striatum MACROALGA EXTRACT AGAINST Pseudomonas Aerugimunosa BACTERIA - Al-Farabi, M. Naufal; Ratna, Isna Sri; Marshanda, Cindy; Putri, Velia Rima; Amelia, Restu; Putri, Elinda Triana (Universitas Muhammadiyah Malang, 2024)
Kappaphycus striatum seaweed is a seaweed better known as